2019
DOI: 10.1111/add.14776
|View full text |Cite
|
Sign up to set email alerts
|

Heavy cannabis use, dependence and the brain: a clinical perspective

Abstract: Aims To summarize and evaluate our knowledge of the relationship between heavy cannabis use, cannabis use disorder (CUD) and the brain. Methods Narrative review of relevant literature identified through existing systematic reviews, meta‐analyses and a PubMed search. Epidemiology, clinical representations, potential causal mechanisms, assessments, treatment and prognosis are discussed. Results Although causality is unclear, heavy and dependent cannabis use is consistently associated with a high prevalence of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 141 publications
(171 reference statements)
1
59
0
3
Order By: Relevance
“…Regarding cannabis use, to our knowledge this is the first MR study to investigate the role of cannabis use in respiratory infections, and while we failed to find evidence of any relationships, smoking cannabis, like tobacco smoking, may prompt the onset of coughing, which could consequently increase viral transmission, or may exacerbate possibly respiratory symptoms. As cannabis is the most used drug worldwide –an estimated 188 million recreational users worldwide 58 – this aspect of cannabis use may have important implications for the spread of COVID-19. In contrast, the single-variable MR CUD results demonstrated adverse effects on several respiratory outcomes, but not COPD, which supports the existing literature; 59-61 however, accounting for lifetime tobacco smoking attenuated highlighting the complex nature of these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cannabis use, to our knowledge this is the first MR study to investigate the role of cannabis use in respiratory infections, and while we failed to find evidence of any relationships, smoking cannabis, like tobacco smoking, may prompt the onset of coughing, which could consequently increase viral transmission, or may exacerbate possibly respiratory symptoms. As cannabis is the most used drug worldwide –an estimated 188 million recreational users worldwide 58 – this aspect of cannabis use may have important implications for the spread of COVID-19. In contrast, the single-variable MR CUD results demonstrated adverse effects on several respiratory outcomes, but not COPD, which supports the existing literature; 59-61 however, accounting for lifetime tobacco smoking attenuated highlighting the complex nature of these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the main pharmacological treatment for OCD is serotonin reuptake inhibitors, and the search for new treatments and growing approval of THC derivatives has produced favorable results in case studies (17). However, we cannot disregard the relationship between cannabis use and the development of dependence (18)(19)(20), which is inheritable, complex, and associated with mental health disorders (21,22). A recent study explored genetic factors associated with lifetime use of cannabis and found ∼35 genes in a sample of more than 180,000 individuals (23).…”
Section: Introductionmentioning
confidence: 99%
“…HIV crosses the blood brain barrier, replicates, and infects cells in the central nervous system (CNS), leading to neuroinflammation and neural degeneration [1][2][3]. Neuroimaging has identified structural and functional brain alterations linked with HIV infection, particularly in frontostriatal circuitry [4][5][6][7][8][9], that are thought to contribute to a spectrum of progressive neurocognitive declines characterizing the disease [10][11][12][13][14][15]. Even with widespread availability of antiretroviral therapy, approximately 30-50% of persons living with HIV (PLWH) are impacted by neurocognitive alterations [16,17].…”
Section: Introductionmentioning
confidence: 99%